2018
DOI: 10.1016/j.joule.2018.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Interfacial Issues in Liquid-Based and Solid-State Batteries by Atomic and Molecular Layer Deposition

Abstract: Solid-state batteries (SSBs) have attracted increasing attention as one of the most promising next-generation batteries. However, various challenges remain for SSBs toward practical applications. Particularly, the interfacial issues between solid-state electrolyte (SSEs) and electrodes are critical factors affecting the performances of SSBs. Atomic and molecular layer deposition (ALD and MLD) are considered as ideal strategies for overcoming the interfacial issues facing SSBs. In the past years, promising prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
128
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(129 citation statements)
references
References 129 publications
(129 reference statements)
1
128
0
Order By: Relevance
“…[17] However,i ts high cost, the rather sophisticated process,a nd its poor ability to transport lithium ions hinder its large-scale application and further development. [18] Herein, we report afacile method to construct apolymeralloy hybrid layer on the Li metal surface (denoted as treated Li)t oi mprove performance and moisture stability.T his process simply involves dipping lithium metal into asolution of 0.1m SnCl 4 in tetrahydrofuran (THF), in which as imple chemical reaction occurs between Li metal and SnCl 4 to form the hybrid layer on the lithium metal surface. [19] Furthermore, propylene oxide (PO) promoted the polymerization reaction to increase the polymer content.…”
mentioning
confidence: 99%
“…[17] However,i ts high cost, the rather sophisticated process,a nd its poor ability to transport lithium ions hinder its large-scale application and further development. [18] Herein, we report afacile method to construct apolymeralloy hybrid layer on the Li metal surface (denoted as treated Li)t oi mprove performance and moisture stability.T his process simply involves dipping lithium metal into asolution of 0.1m SnCl 4 in tetrahydrofuran (THF), in which as imple chemical reaction occurs between Li metal and SnCl 4 to form the hybrid layer on the lithium metal surface. [19] Furthermore, propylene oxide (PO) promoted the polymerization reaction to increase the polymer content.…”
mentioning
confidence: 99%
“…In situ optical microscopy observations confirmed that the Li x Si‐modified Li anode showed dendrite‐free Li dissolution/deposition behavior, whereas a bare Li electrode suffered with obvious dendrite growth. The developments and understandings of MLD and ALD techniques for applications in batteries have been well reviewed recently …”
Section: Strategies For Developing Stable LI Metal Anodesmentioning
confidence: 99%
“…28,29 To solve the interface problem of SE, many works have been focused on the modification of interfacial transition layers. Inorganic oxides, 30,31 carbon, 32 fluoride, 33 nitride, 6,34 polymer, [35][36][37] and their composites 23,38,39 were successively applied to Li anodes, showing good results in inhibiting Li dendrite growth and regulating Li uniform deposition. However, it is a difficulty to make modification directly on the surface of lithium metal because of its high vivacity.…”
Section: Introductionmentioning
confidence: 99%